Computer simulation and field study of the stress-strain state of the biomechanical system «fixator-bone» at supramalleolar corrective osteotomies - Omelchenko, Taras; Buryanov, Oleksandr; Lyabakh, Andriy; Shidlovkiy, Mykola; Yeshchenko, Viktor; Dyman, Mariana (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2019)
Objective: to study the stability of internal fixation at various types of the supramalleolar corrective osteotomies of the distal tibia bone. To examine the parameters of stiffness and durability of the «fixator-bone» systems at computer simulation by finite elements method; to assess the adequacy of this method by comparisons with the results of field full-scale studies. Methods: the 3D distal tibia bone model is based on the CT of an intact tibia in the ANSYS software package. In-situ study we used 5 intact distal tibia bone species of dead people. In the models we recreated supramalleolar corrective osteotomies specified zones with fixation with various blocked plates with angular stability. Results: systems with medial blocked «puddi-plate» and anterior lateral blocked L-shaped plates had the highest stiffness and stability. The allowable efforts for compression were 217 and 308 N, for bending — 34 and 73 N, for torsion — 18.8 and 17.9 N/m, respectively. The smallest compressive stiffness (151 N), bending (19 N) and torsion (2.46 N/m) were found at a medial blocked plate. Similar distribution of maximal static and cyclic loads was obtained in full-scale bench research. Conclusions: the adequacy of imitation 3D-models and parameters of biological materials incorporated in them was confirmed. In the case of a medial supramalleolar corrective osteotomies with an open wedge, the medial blocked plate «puddi-plate» provided the greatest stability and rigidity of fixation. For lateral supramalleolar corrective osteotomies with closed wedge and anterior focal dome correcting osteotomies — optimally used anterior-lateral L-shaped blocked plate.